Risk of burnout syndrome associated with physicians working in the emergency area during the pandemic of Covid-19 in Brazil - Benincá, Vitor; Souzbach, Louyze; Hortêncio de Melo, Rafael; Ioppi Zugno, Alexandra (LAJEC - Latin American Journal of Emergency Care, 2023)
Objective: To verify the risk of burnout syndrome in physicians working in the emergency area during the pandemic of Covid-19 in Brazil. Methods: A prospective cohort was carried out using two questionnaires (adapted clinical and Maslach Burnout Inventory) that were sent in two moments, during a period of high incidence of the disease, also called peak, and in a second moment when the pandemic was already under control. Results: The median age was 38.5 years, with a standard deviation of 7.83. Regarding gender, 62% were women. Most (55%) were married. Good portion consuming alcohol regularly during the week. In 2021, the period with the highest number of Covid-19 cases, the burnout level was 51.36, with a standard deviation of 16.48. Subsequently, in 2022, the period with the lowest impact of Covid-19 on attendances, the level decreased to 48.78, with a standard deviation of 15.49. Conclusions: The pandemic was an independent factor associated with the worsening mental health of physicians working on the front lines of the Covid-19 pandemic.